CORRECTION OF PARTIAL DEFECTS OF THE EXTERNAL EAR - Y.P. Nagirnyi (Український стоматологічний альманах, 2018)
In foreign literature plastic surgery provides this classification of traumatic ear defects: a complete loss of the ear, ear partial defects, including conventionally distinguished defects: the top third of the ear, the middle third of the ear, the lower third of the ear.